Antifungal Potential of Sonchus oleraceus and Lactuca virosa Extracts Against Fusarium verticillioides, the Causal Agent of Damping-Off in Sweet Corn in Iraq - Alyaa Abd Ali; Ayoob Obaid Alfalahi; Aalaa Khudhair Hassan (Zanco Journal of Pure and Applied Sciences)
A factorial experiment was conducted under laboratory conditions to evaluate the inhibitory effect of ethanomethanolic extracts of Sonchus oleraceus L. and Lactuca virosa L. against Fusarium verticillioides and Fusarium oxysporum causing root and crown rot disease in sweet corn. The GC-MS analysis indicated diverse phytochemicals in both plant types, however, S. oleraceus had more active components than L. virosa. In general, Tetracosane, Bis(2-ethylhexyl) phthalate and Nonadecane are the dominant active components. The results of pathogenicity revealed that the isolated fungi were pathogenic to sweet corn, as both led to significant increase (p ≤ 0.05) in the percentage of infection. However, the F. verticillioides isolate had the highest infection percentage of 85.00% with significant differences (p ≤ 0.05) compared to the control group. Results of the antagonistic effect showed that the ethanomethanolic extract of S. oleraceus had the highest significant inhibitory percentages (p ≤ 0.05) against both Fusarium isolates. Furthermore, positive relationship between the investigated concentrations and the inhibition percentage towards the maximum concentration of 9 mg/mL that revealed 100% inhibition capacity. The concentration of 7% reported an inhibition rates against F. verticillioides of 87% and 81% for each of S. oleraceus and L. virosa extracts, respectively. Also, the 7 mg/mL concentration significantly reduced the radial growth of F. oxysporum fungi causing an inhibition rates of 90% and 78%, respectively. Further investigation would be valuable in precise characterization of active compounds and developing them into more sustainable fungicides.